PERAN ZAKAT PRODUKTIF DALAM MENINGKATKAN KESEJAHTERAAN PEDAGANG KAKI LIMA (MUSTAHIK) KOTA LHOKSEUMAWE - Yunus, Muhammad; Syahriza, Mulkan (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2024)
Zakat is one of the basic obligatory acts of worship which is carried out by giving some of a person's assets to people who are entitled to receive them with the aim of realizing social justice in society in general. With its form of giving, zakat is often considered to only provide momentary benefits and tends to be consumptive in nature. However, zakat can also take the form of gifts that can provide long-term benefits that tend to be productive. This study explains how mustahik use zakat funds with the final result being a solution that can be implemented by Baitul Mal Lhokseumawe City in increasing the use of productive zakat to improve the welfare of street vendors (mustahik) in their area. The research method used is empirical juridical through observations and interviews with Baitul Mal related to zakat. Based on the results of research that has been carried out, the management of productive zakat in Baitul Mal Lhokseumawe City needs to be improved, especially when carrying out the controlling or supervising function of zakat that has been given to street vendors (mustahiq).